BIOMASS RESEARCH IN INDIA: MEASURING SCIENTIFIC GROWTH AND GLOBAL LINKAGES THROUGH SCIENTOMETRICS - Chaparwal, Naveen; P S Rajput (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study presents a Scientometric analysis of biomass research in India period from 2013 to 2022. By utilizing bibliographic data from the Scopus database, the research investigates the growth, key contributors, institutional impact, funding sources, and emerging trends. The analysis reveals a significant increase in research output, with a notable rise in publications, underscoring the growing importance of biomass as a sustainable energy source in India. Key research themes identified through Multiple Correspondence Analysis (MCA) include biofuels, microalgae, and carbon management, which are central to the field. Author impact analysis highlights a group of influential researchers whose work has substantially shaped the biomass research landscape. Institutional contributions are led by Banaras Hindu University and the Indian Institutes of Technology, which are at the forefront of this research area. The co-authorship network analysis reveals strong collaboration between Indian institutions and international partners, contributing to the global advancement of biomass research.